2011
DOI: 10.1021/es103359f
|View full text |Cite
|
Sign up to set email alerts
|

Blinded Taste Panel Evaluations To Determine if Fish from near the Oil Sands Are Preferred Less than Fish from Other Locations in Alberta, Canada

Abstract: The oil sands industry is rapidly expanding surface mining and bitumen extraction operations near the Athabasca River in northeastern Alberta, Canada. There are anecdotal comments that the fish from the Athabasca River have an off-taste, implying that the oil sands operations are the cause. This study was done to determine if the taste of wild fishes caught near the Athabasca oil sands was less preferred than the taste of fishes collected from two other river basins in Alberta. In blinded experiments, consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Each solution was administered twice in random order and the still water was used as a control substance. After every stimulus, subjects were invited to rinse their mouth with water and to eat unsalted crackers in order to recover a neutral taste sensation on their tongue [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each solution was administered twice in random order and the still water was used as a control substance. After every stimulus, subjects were invited to rinse their mouth with water and to eat unsalted crackers in order to recover a neutral taste sensation on their tongue [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Potential impacts of oil sands development on the health of organisms, including fishes, and subsequent consumption have motivated much of the research attention in the region (Miall, 2013 ). While blinded panels were unable to differentiate the taste of steamed samples of fishes captured from three locations in Alberta, including the Athabasca River (Barona et al, 2011 ), oily and soft flesh of fish has been reported by residents downstream of the oil sands area (Timoney & Lee, 2009 ) and from Cold Lake (Brunet et al, 2020 ). Physical abnormalities in fishes have also been noted by residents (Brunet et al, 2020 ; Miall, 2013 ; Timoney & Lee, 2009 ).…”
Section: Literature Reviewmentioning
confidence: 99%